Correlation of Endostatin and Tissue Inhibitor of Metalloproteinases 2 (TIMP2) Serum Levels With Cardiovascular Involvement in Systemic Sclerosis Patients - Bozena Dziankowska-Bartkowiak; Elzbieta Waszczykowska; Anna Zalewska; Anna Sysa-Jedrzejowska (Hindawi Limited, 2005)
Fibrosis of oesophagus, lungs, heart, and kidney in the course of systemic sclerosis (SSc) may lead to dysfunction of the above organs or even patients death. Recent studies point out the role of angiogenesis and fibrosis disturbances in the pathogenesis of SSc. Heart fibrosis is one of the most important prognostic factors in SSc patients. So, the aim of our study was to examine cardiovascular dysfunction in SSc patients and its correlation with serum levels of vascular endothelial growth factor (VEGF), endostatin, and tissue inhibitor of metalloproteinase 2 (TIMP2). The study group comprised 34 patients (19 with limited scleroderma (lSSc) and 15 with diffuse scleroderma (dSSc)). The control group consisted of 20 healthy persons, age and sex matched. Internal organ involvement was assessed on the basis of specialist procedures. Serum VEGF, endostatin, and TIMP2 levels were evaluated by ELISA. We found cardiovascular changes in 15 patients with SSc (8 with lSSc and 7 with dSSc). The observed symptoms were of different characters and also coexisted with each other. Higher endostatin serum levels in all systemic sclerosis patients in comparison to the control group were demonstrated (P<.05). Also higher serum levels of endostatin and TIMP2 were observed in patients with cardiovascular changes in comparison to the patients without such changes (P<.05). The obtained results support the notion that angiogenesis and fibrosis disturbances may play an important role in SSc. Evaluation of endostatin and TIMP2 serum levels seems to be one of the noninvasive, helpful examinations of heart involvement in the course of systemic sclerosis.